Public Service Management in Rural Primary Health Care: Organizational Capacity, Standard Operating Procedure Compliance, and Community Outreach in Indonesia - Nartin; Jefry Crisbiantoro; Jabal Arfah; Hasjad; Melati (Global Research Collaboration, 2026)
Rural primary health care facilities must deliver public services under resource constraints, diverse service needs, and uneven community health awareness. In Indonesia, Puskesmas functions not only as a first-level health care facility, but also as a public service organization that must manage resources, standard operating procedures, service communication, and community outreach. This study analyzes public service management in rural primary health care by examining organizational capacity, standard operating procedure compliance, implementer disposition, community outreach, and cross-sector coordination at Mowewe Puskesmas, East Kolaka Regency, Indonesia. Methods: A descriptive qualitative case study was conducted from April to May 2026. Sixteen informants were selected through purposive sampling and limited snowball sampling, including managers, health workers, administrative staff, health cadres, and service users. Data were collected through observation, in-depth interviews, and review of standard operating procedure documents. The data were analyzed using the Miles and Huberman interactive model through data reduction, data display, and conclusion drawing. Findings: The findings show that Mowewe Puskesmas provides curative, preventive, promotive, and rehabilitative services based on regulations and standard operating procedures. Health worker commitment, mobile outreach services, and health cadres support service delivery. However, limited human resources, suboptimal facilities, low community health awareness, and irregular cross-sector coordination constrain service effectiveness. This study contributes an empirical model that links organizational capacity, standard operating procedure compliance, implementer disposition, community outreach, and cross-sector coordination as interrelated determinants of rural primary health care effectiveness. The findings support managerial action on workforce planning, procedure evaluation, facility improvement, cadre development, mobile service scheduling, and routine cross-sector coordination.